INSTRUCTIONAL THOUGHTS ABOUT HUMANITY IN THE CREATIVITY OF THE KYRGYZ AKYNS OF THE XIX-XX CENTURIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article examines the humanistic ideas in the poems Zhenizhok, Toktogul, Togolok Moldo and Barpy and explores their relationship to nature. The author’s songs by Zhenizhok, Toktogul, Togolok Moldo and Barpy discuss educational value, good and evil, justice and injustice, humanistic thoughts and love. The meaning of the verses of poets that have come down to us is written in a language accessible to the current generation, and humanity, concern for the universe, nature, worldview - everything is interpreted and compared in a single way.
Keywords: justice, injustice, good and evil, humanity.